98.8k views
2 votes
For the following system, use the second equation to make a substitution for x in the first equation.

x + 5y - 10 = 0
x = 2y - 8

What is the resulting equation in simplest form?

User Zap
by
5.0k points

2 Answers

2 votes

Answer:

Replace x with 0 and simplify.x,x+5y- 10=0, x = 2 y − 8

Explanation:


User DejanRistic
by
5.0k points
5 votes

Answer:

The resulting equation is
2y-8 + 5y - 10 = 0

Explanation:

For the following system, use the second equation to make a substitution for x in the first equation.


x + 5y - 10 = 0 first equation


x = 2y - 8 second equation

Now substitute the second equation in first equation

Replace x with 2y-8 in first equation


x + 5y - 10 = 0


2y-8 + 5y - 10 = 0

The resulting equation is
2y-8 + 5y - 10 = 0